2023
DOI: 10.1001/jamanetworkopen.2022.55631
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Associations Between Adiposity and Cognitive Function and Mediation by Brain Morphology in the ABCD Study

Abstract: ImportanceMost epidemiologic studies examine the brain as an outcome in relation to adiposity (ie, the brain-as-outcome perspective), but it is also a potential risk factor associated with adiposity accumulation over time (ie, the brain-as–risk factor perspective). The bidirectionality hypothesis has not been fully explored in adolescent samples previously.ObjectiveTo assess bidirectional associations between adiposity and cognitive function in youth and test mediational pathways through brain morphology (spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Independent of fitness and activity levels, body composition, particularly body fatness, has also been hypothesized to contribute to changes in brain volume and cognitive function. For example, higher BMI has been associated with decreased gray matter volume across multiple brain regions (14), and links between central adiposity, as measured by waist circumference, and executive function have been observed both in children (15) and older women (16). Recent systematic reviews of cross-sectional studies have indicated that obesity, particularly central obesity, is commonly correlated with reduced cortical thickness and gray matter volume (17) and with cognitive impairment in older adults (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of fitness and activity levels, body composition, particularly body fatness, has also been hypothesized to contribute to changes in brain volume and cognitive function. For example, higher BMI has been associated with decreased gray matter volume across multiple brain regions (14), and links between central adiposity, as measured by waist circumference, and executive function have been observed both in children (15) and older women (16). Recent systematic reviews of cross-sectional studies have indicated that obesity, particularly central obesity, is commonly correlated with reduced cortical thickness and gray matter volume (17) and with cognitive impairment in older adults (18).…”
mentioning
confidence: 99%
“…Recent systematic reviews of cross-sectional studies have indicated that obesity, particularly central obesity, is commonly correlated with reduced cortical thickness and gray matter volume (17) and with cognitive impairment in older adults (18). However, prospective longitudinal studies in both children (15) and midlife adults (19) have observed a bidirectional predictive relationship between cognition and central obesity indicating that there may be a common causal pathway contributing to the development of both conditions. Kullmann et al (20) may have identified at least some portion of this shared pathway, noting that insulin sensitivity in the brain is strongly associated with volume of visceral fat, and insulin (in)sensitivity is associated with cognitive capacity.…”
mentioning
confidence: 99%
“…In the Original Investigation titled “Bidirectional Associations Between Adiposity and Cognitive Function and Mediation by Brain Morphology in the ABCD Study,” 1 published February 16, 2023, there are errors in the units of waist circumference in Table 1 and in the Methods section. There units were written as centimeters but should be inches.…”
mentioning
confidence: 99%